Environmental Graphic Design (EGD) to enhance experiential learning about forestry among the younger generation / Junidsyazji Basharuddin - Basharuddin, Junidsyazji (2022)
The lack of forestry knowledge and awareness as well as declining interest in learning about the forest and its resources is evident among the younger generation. This problem was brought to light by Director General of Forest Reserve Institute Malaysia (FRIM) upon looking at a steady decrease in research activities at the campus facilities. This is confirmed by the lack of awareness in caring after the trees and grounds at the FRIM campus whereby trees (younglings and mature) are intentionally roughened, plucked and mutilated. This shows there is a need to address the issue of forestry awareness especially among the younger visitors for the sake of sustainability. Therefore, this study aims to discover ways to increase interest in learning about forestry knowledge among the younger generation through the use of Environmental Graphic Design (EGD). This research employs multi-stage approach, whereby the use of theories is to design methodology that suits purpose and objectives of the study. Survey method is used to achieve the aim and its objectives, where questionnaire sets were designed through knowledge understanding via analysis of existing theories and ideas from literatures and interview sessions. The study is further developed based on data gathered from questionnaire that surveyed public attitudes towards Graphic Design Elements as well as the respondents' preferred learning styles.